8th International Multitopic Conference, 2004. Proceedings of INMIC 2004.
DOI: 10.1109/inmic.2004.1492858
|View full text |Cite
|
Sign up to set email alerts
|

Speaker recognition using lower formants

Abstract: Speaker recognition is the areu ofspeech teechnoloa, which atfem@r to identfy the speukeu. There are hvn distinct uppuuaches in fhis domain. One is bused on hlind DSP prnceming where we deal wifh the signal regardless of its content. The other is phonetic based where indviihal phonemic unity are identij'ied processed and niafched on (he basis of cevtuin,fiatures. Our vestarch is relafed lo the second approach and we have iried io ideiifjfi high level phonemic fearuves Iike sfyle etc. from the pocessing of lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…On the other hand, spectral level has been extensively used in speaker recognition systems for feature extraction. Typical methods in this spectral level are as follows: Short-time spectrum (no matter if we use the exact representation or its approximation by filter banks) (Xiang and Berger, 2003 ; Seddik et al, 2004 ; Burget et al, 2007 ), predictor coefficients [based on a linear model of speech production: (Park et al, 2006 )], formant frequencies and bandwidth [defined as the resonance frequencies of the vocal tract: (Fatima et al, 2004 )], or even the formant trajectories (Tanabian et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, spectral level has been extensively used in speaker recognition systems for feature extraction. Typical methods in this spectral level are as follows: Short-time spectrum (no matter if we use the exact representation or its approximation by filter banks) (Xiang and Berger, 2003 ; Seddik et al, 2004 ; Burget et al, 2007 ), predictor coefficients [based on a linear model of speech production: (Park et al, 2006 )], formant frequencies and bandwidth [defined as the resonance frequencies of the vocal tract: (Fatima et al, 2004 )], or even the formant trajectories (Tanabian et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study of formant contours at consonant-vowel boundary shows that a speaker can be identified using the consonant to vowel transition information. The speaker information at the transition was named the "speaker-style" [11]. The biannual National Institute of Standards and Technology (NIST) Speaker Recognition Evaluation (SRE) also presents the optional test of 10-second evaluation [12].…”
Section: A Background and Literature Reviewmentioning
confidence: 99%
“…The length of utterance in most of these cases is around 10 seconds. Other than [10] and [11], most of the researches make use of utterances no less than 2 seconds. In light of these researches, we strive to find the usefulness of phonemes in speaker recognition using utterance length equal to the size of a long vowel.…”
Section: A Background and Literature Reviewmentioning
confidence: 99%